2014
DOI: 10.1007/s10152-014-0387-2
|View full text |Cite
|
Sign up to set email alerts
|

The barred grunt Conodon nobilis (Perciformes: Haemulidae) in shallow areas of a tropical bight: spatial and temporal distribution, body growth and diet

Abstract: This study aimed to comprehensively investigate the population biology of Conodon nobilis (Perciformes, Haemulidae) in Caraguatatuba Bight, southeastern Brazil. Monthly trawls were performed from October 2003 through October 2004 in two areas of the bight that are similar to but distant from each other, South and North. For all specimens, the size was measured and the sex and reproductive stage identified. Abundance and size were compared over areas and months. Body growth parameters were parameterized accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
6
1
1
Order By: Relevance
“…In the presently reported study, high FI values were found, indicating an intense use of the environment as a feeding area. Previous studies on the feeding habits of this species Oliveira-Silva 1998, Vasconcelos Filho et al 2010) in Itamaracá Island, northeast part of Brazil and Caraguatatuba Bight, south-eastern Brazil (Pombo et al 2014) have shown that their main prey items are crustaceans. Similar results were observed in the presently reported study, with C. nobilis classified as a zoobenthivore, feeding on crustaceans, mainly shrimps of the family Penaeidae.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In the presently reported study, high FI values were found, indicating an intense use of the environment as a feeding area. Previous studies on the feeding habits of this species Oliveira-Silva 1998, Vasconcelos Filho et al 2010) in Itamaracá Island, northeast part of Brazil and Caraguatatuba Bight, south-eastern Brazil (Pombo et al 2014) have shown that their main prey items are crustaceans. Similar results were observed in the presently reported study, with C. nobilis classified as a zoobenthivore, feeding on crustaceans, mainly shrimps of the family Penaeidae.…”
Section: Discussionmentioning
confidence: 89%
“…Size differences between months may be related to the level of exploitation in the area, the ecological characteristics of each region, and the differential selectivity of the fishing gear (Frédou et al 2009). Along the southern coast of Pernambuco, the maximum lengths recorded (27.5 cm) for C. nobilis were greater than those recorded for the same species in other areas, e.g., 15 cm in Caraguatatuba Bay, São Paulo (Brazil) (Pombo et al 2014), 12 cm in Rio Grande do Norte (Brazil) (Garcia et al 2010), and 26 cm in the Gulf of Salamanca (Colombia) (Garcia et al 1998). Although the results of the presently reported study may be hampered by the selectivity of the fishing gear, based on the habitat of the species (shallow muddy bottoms) and the L max reported (33.6 cm TL, Cervigón et al 1992), which is near to the range of individuals caught in the presently reported study (6.6 to 27.5 cm TL, including juveniles and adults), we assumed that our sampling adequately covered the size and behaviour of the species, and the parameters provided here are representative of the C. nobilis population in northeast Brazil.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Ikan gerot-gerot termasuk dalam Famili Haemulidae yang merupakan jenis ikan demersal dan dinamai grunt karena menghasilkan suara yang berasal dari gesekan gigi dan diperkuat oleh gelembung renang (Pambo et al, 2014). Ciri khas ikan tersebut yaitu: bentuk tubuh pipih, kepala cembung, dagu memiliki dua pori-pori di setiap sisinya yang diikuti dengan lubang yang terletak pada bagian anterior, dan panjang tubuh maksimal 800 mm (McKay, 2001).…”
unclassified